Effects of core training on muscular power of handball goalkeepers - Camacho Cardeñosa, M.; Camacho Cardeñosa, A.; Moldón Espartero, J.; Crespo Coco, C.; Olcina, G.; Timón, R. (Revista Ciencia del Deporte, 2019)
Goalkeeper efficacy is a very important performance variable, due to handball is a finalization sport, that is, each action finishes in a throw or action next to opposite goal. Therefore, goalkeeper training should be individual and specific. This position needs methods of training, methodology and control that adapted to goalkeeper. Currently, some coaches used to apply training design that is not pay attention to this specificity. The aim of this study was to investigate the effect of a physical-technique training on muscular power of handball goalkeeper. Four senior male goalkeepers performed for 4 weeks a strength-stability core training program. Jump performance, upper and lower limb power and strength Core were measured before and after the training period. Significant improvements in performance variables were not observed. In summary, the main findings of the study indicated that 12 sessions of physical-technique training did not result in any improvement muscular power on handball goalkeeper performance. More studies are needed on a larger sample of goalkeepers and to study the evolution of these variables in the long term.